Treatment of severe flares in Crohn’s disease and ulcerative colitis Therapie des schweren Schubs bei Morbus Crohn und Colitis ulcerosa - Stallmach, Andreas; Stallhofer, Johannes; Schmidt, Carsten; Atreya, Raja; Grunert, Philip C. (Innere Medizin, 2025)
Background: In chronic inflammatory bowel diseases (IBD), severe flares are characterized by intense inflammatory activity and a high disease burden for patients. Treatment addresses both short-term goals (e.g., symptom reduction, prevention of complications) and long-term goals (sustained clinical steroid-free remission and healing of inflammatory lesions, known as “mucosal healing”). Objective of the study: To present evidence-based, targeted diagnostics and stepwise treatment of severe flares in Crohn’s disease (CD) and ulcerative colitis (UC), in order to prevent complications, including mortality, and to achieve rapid remission. Materials and methods: Selective literature review, including German and European guidelines for the treatment of severe flares. Results and discussion: After ruling out complications (e.g., infections, strictures, abscesses, toxic megacolon), based on a structured assessment of disease severity, intravenous steroid therapy is indicated in severe acute flares for both CD and UC, which should lead to improvement within the first 72 h. If no improvement occurs, medical therapy must be intensified. Various therapeutics, including biologics targeting tumor necrosis factor (TNF)-α, α4ß7 integrins, interleukin (IL)-12/23 or IL-23, as well as Janus kinase (JAK) inhibitors, sphingosine 1‑phosphate receptor (S1PR) modulators, and calcineurin inhibitors, are available today, but there is no clear algorithm preferring one drug for CD or UC. Instead, treatment should be selected based on approvals, the patient’s medical history, prior treatment, risk profile, and potential complications. Surgical options must always be considered as part of close interdisciplinary care.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Biological products; Infections; Inflammatory bowel diseases/complications; Inflammatory bowel diseases/severe flares; Intravenous steroid therapy